Preparation method of phytic alkene carbon nanomaterial and application of phytic alkene carbon nanomaterial in photovoltaic field
By making biomass powder into phytoensis carbon nanomaterials and applying them to photovoltaic synergists, the difficulties in industrialization of carbon nanomaterials and the problem of unexplored biomass resources are solved, and the efficient photoelectric conversion of photovoltaic panels is achieved.
Patent Information
- Application Number
- CN202510064835.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-22
AI Technical Summary
In the prior art, the industrialization of carbon nanomaterials faces the problems of difficulty in collecting and low yield. At the same time, biomass by-products and waste have not been effectively developed, which limits the development of clean, efficient and high value-added photovoltaic technology.
Biomass powder is used as raw materials, and phytoensis carbon nanomaterials are prepared through carbon production, primary electrolysis, ultrasonic peeling and microwave circulation treatment, and used for photovoltaic synergist coating or combined with photovoltaic substrates to improve the photoelectric efficiency of photovoltaic panels.
The efficient preparation of carbon nanomaterials and the photoelectric efficiency of photovoltaic panels have been achieved, with an efficiency of up to 5%-15%, and at the same time, it provides a new path for the comprehensive utilization of biomass resources.
Smart Images

Figure CN119858911A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of preparation of carbon nanomaterials, in particular to a phytoene carbon nanomaterial and a preparation method thereof and application thereof in the field of photovoltaic efficiency enhancement. Background Art
[0002] Carbon is one of the most important elements in nature and closely related to human beings. Researchers have found that carbon nanomaterials, including carbon quantum dots, graphene quantum dots, fullerenes, carbon nanotubes, digraphene, graphene oxide and other nanomaterials, all have excellent electrical and thermal conductivity, stable chemical properties and good thermal stability, which has aroused unprecedented research enthusiasm among researchers in both scientific materials and technology fields.
[0003] Nanomaterials can be divided according to their dimensions: carbon quantum dots, graphene quantum dots and fullerenes are all zero-dimensional materials; one-dimensional carbon nanomaterials, typically represented by carbon nanotubes, carbon nanofibers, etc., generally have a diameter of nanometers and a length of micrometers; two-dimensional carbon nanomaterials, the most typical of which is graphene, have a thickness of about a few nanometers and a maximum sheet diameter of centimeters; three-dimensional carbon nanomaterials, such as graphene sponges, carbon nanotube sponges, etc., are generally bulk nanomaterials constructed from one-dimensional or two-dimensional nanomaterials.
[0004] At present, there are still many problems to be solved in realizing the industrialization of carbon nanomaterials. One of the more important points is that carbon nanomaterials are difficult to collect and the output is low.
[0005] Various industries that use animals and plants as raw materials will generate tens of billions of tons of biomass byproducts and waste, most of which are untapped. These biomass wastes are used as alternative resources to convert biomass into syngas, bio-oil and biochar through gasification or pyrolysis. Syngas and bio-oil can replace fossil fuels as biofuels and alleviate the problem of energy depletion. But they will eventually be converted into carbon dioxide, which is not harmonious with the environment and hinders the industrialization of this technology. At present, the photoelectric efficiency of silicon-based or organic photovoltaics is close to that of single-junction cells SQ pole. After decades of development, the photoelectric efficiency has been rising, reaching 26% in the laboratory and 24.5% on average in photovoltaic power plants.
[0006] Therefore, attempts have been made in this field to convert biochar into carbon nanomaterials and apply them to the photovoltaic field, thereby developing clean, efficient and high value-added photovoltaic products and releasing the economic potential of biochar. Summary of the invention
[0007] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a method for preparing phytoene carbon nanomaterials and their application in the photovoltaic field, so as to solve the problems raised in the above background technology.
[0008] To achieve this object, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a method for preparing a biomass carbon nanomaterial. The preparation method uses biomass powder as raw material, obtains a biochar suspension after charcoal making and primary electrolysis, and then obtains the biomass carbon nanomaterial through secondary electrolysis, ultrasonic stripping and microwave cycle treatment.
[0010] The preparation method provided by the present invention uses biochar as raw material and adopts electrolysis, ultrasound and microwave circulation method to prepare carbon nanomaterials, which is different from the conventional hydrothermal synthesis method. No chemical reagents are added. The prepared carbon nanomaterials have good fluorescence properties. The carbon nanomaterials are made into photovoltaic enhancer coatings and applied to silicon-based photovoltaic panels or combined with photovoltaic substrates, which can significantly improve the photoelectric efficiency of photovoltaic panels.
[0011] As a preferred technical solution of the present invention, the biomass powder is derived from any one of plant biomass, animal biomass, factory biomass or urban waste biomass, or a combination of at least two of them.
[0012] Preferably, the biomass powder is plant biomass, and the carbon nanomaterial prepared using plant biomass as raw material is phytoene carbon nanomaterial.
[0013] In the present invention, the carbon nanomaterial obtained by using the plant biomass is the "phytoene" carbon nanomaterial. Phytoene, a carbon nanomaterial extracted from plants and similar to "graphene", is a new type of material that can provide energy.
[0014] Preferably, the biochar is apricot biochar (XZC), rice straw biochar (DZC) or ganoderma lucidum biochar (LZC).
[0015] Preferably, the biochar obtained after carbonization of the biomass powder is carbon powder, carbon rod or carbon plate.
[0016] In the present invention, the biomass powder can be put into water for ultrasonic cleaning, and then dried to remove impurities, and then made into carbon powder, carbon rod or carbon plate through a carbon making process.
[0017] As a preferred technical solution of the present invention, the method for preparing biomass carbon nanomaterials provided by the present invention comprises the following steps:
[0018] Step S1, ultrasonically clean the biomass powder to remove impurities and then dry it to obtain biochar after charring;
[0019] Step S2, electrolyzing the biochar obtained in step S1, and stirring to form a suspension;
[0020] Step S3, subjecting the suspension obtained in step S1 to secondary electrolysis, ultrasonic stripping and microwave circulation treatment, and then centrifugally separating the suspension to remove non-fluorescent precipitates to obtain a solution containing the biomass carbon nanomaterial.
[0021] As a preferred technical solution of the present invention, the power of ultrasonic cleaning in step S1 is 500-1000 W, for example, it can be 500 W, 600 W, 700 W, 800 W, 900 W or 1000 W, etc.; the frequency is 20-40 kHz, for example, it can be 20 kHz, 25 kHz, 30 kHz, 35 kHz or 40 kHz, etc.; the time is 30-60 min, for example, it can be 30 min, 35 min, 40 min, 45 min, 50 min or 60 min, etc.
[0022] Preferably, the carbon making method in step S1 is: under protective gas or vacuum conditions, the biomass powder is pressed into powder, rods or plates by a hydraulic press, and then carbonized and graphitized to complete the carbon making step.
[0023] In the present invention, the carbon making method is as follows: under protective gas or vacuum conditions, biomass powder or biomass powder is pressed into powder rods or plates by a 50-ton hydraulic press, and then processed by a carbonization and graphitization integrated furnace.
[0024] As a preferred technical solution of the present invention, the power of the primary electrolysis in step S2 is 100-1500W, for example, it can be 100W, 200W, 300W, 400W, 500W, 600W, 700W, 800W, 900W, 1000W, 1100W, 1200W, 1300W, 1400W or 1500W, etc.; the voltage is 0.01-48V, for example, It is 0.01V, 0.05V, 1V, 2V, 5V, 10V, 15V, 20V, 25V, 30V, 35V, 40V or 48V, etc.; the current is 0.01-30A, for example, it can be 0.01A, 1A, 2A, 5A, 10A, 15A, 20A, 25A or 30A, etc.; the duration is 2-7 days, for example, it can be 2 days, 3 days, 4 days, 5 days, 6 days or 7 days.
[0025] As a preferred technical solution of the present invention, in step S3, the secondary electrolysis power is 100-1500W, for example, it can be 100W, 200W, 300W, 400W, 500W, 600W, 700W, 800W, 900W, 1000W, 1100W, 1200W, 1300W, 1400W or 1500W, etc.; the voltage is 0.01-48V, for example, it can be 0.01V, 0.05V, 1V, 2V, 5V, 10V, 15V, 20V, 25V, 30V, 35V, 40V or 48V, etc.; the current is 0.01-30A, for example, it can be 0.01A, 1A, 2A, 5A, 10A, 15A, 20A, 25A or 30A, etc.
[0026] Preferably, the power of the ultrasonic stripping in step S3 is 500-1000 W, for example, it can be 500 W, 600 W, 700 W, 800 W, 900 W, 1000 W, 1100 W, 1200 W, 1300 W, 1400 W or 1500 W, etc.; the frequency is 20-40 kHz, for example, it can be 20 kHz, 25 kHz, 30 kHz, 35 kHz or 40 kHz, etc.
[0027] Preferably, the power of the microwave in step S3 is 300-1500 W, for example, it can be 300 W, 400 W, 500 W, 600 W, 700 W, 800 W, 900 W, 1000 W, 1100 W, 1200 W, 1300 W, 1400 W or 1500 W, etc.
[0028] Preferably, in step S3, the secondary electrolysis, ultrasonic stripping and microwave are cyclically performed for a total period of 24-60 days, for example, 24 days, 25 days, 28 days, 30 days, 35 days, 39 days, 40 days, 42 days, 45 days, 48 days, 51 days, 54 days, 57 days or 60 days.
[0029] In the present invention, the biomass carbon nanomaterial can be prepared by the following method:
[0030] Step S1, putting the biomass powder into water for ultrasonic cleaning for 60 minutes, removing impurities and then drying, and obtaining carbon powder, carbon rod or carbon plate after carbonization;
[0031] Step S2, directly electrolyzing the carbon powder, carbon rod or carbon plate obtained in S1, with an electrolysis power of 800±50W, a voltage of 36±2V, a current of 15±1A, and a duration of 4±1 days; and stirring to form a black suspension;
[0032] Step S3, the suspension is subjected to secondary electrolysis, with an electrolysis power of 800±50W, a voltage of 36±2V, and a current of 15±1A; then ultrasonic stripping is performed, with a power of 700±30W and a frequency of 30±10Hz; and then microwave cycle treatment is performed, with a microwave power of 1500W;
[0033] The total duration of the electrolysis, ultrasound, and microwave cycles was 40 ± 5 days.
[0034] In the present invention, the electrolysis, ultrasound and microwave treatments are performed in a cycle, and the treatment time is equal. For example, ultrasonic stripping is performed after 1 hour of electrolysis, and microwave treatment is performed after 1 hour; or ultrasonic stripping is performed after 12 hours of electrolysis, and microwave treatment is performed after 12 hours; the three are performed in a cycle, and the total treatment time is 40±5 days.
[0035] Alternating treatments of electrolysis, ultrasound and microwaves can make the biomass in the solution more component-rich and the particle size distribution more uniform.
[0036] The suspension is then separated by centrifugation to remove non-fluorescent precipitates without subsequent addition of chemical reagents, thereby obtaining a carbon nanomaterial solution.
[0037] In a second aspect, the present invention further provides a biomass carbon nanomaterial prepared using the preparation method described in the first aspect.
[0038] Among them, the apricot phytoene carbon nanomaterial prepared from apricot biomass has an average particle size of 2.08±0.50nm and is relatively dispersed;
[0039] The rice phytoene carbon nanomaterials prepared from rice biomass have an average particle size of 3.05±0.30nm and are relatively dispersed;
[0040] The Ganoderma phytoene carbon nanomaterial prepared from Ganoderma biomass has an average particle size of 1.5±0.20nm and is relatively concentrated in distribution.
[0041] In a third aspect, the present invention provides the application of the biomass carbon nanomaterial as described in the second aspect in photovoltaics.
[0042] Preferably, the photovoltaics are silicon-based photovoltaics, organic thin-film photovoltaics, or perovskite photovoltaics.
[0043] Preferably, the photovoltaic application includes the following: making the biomass carbon nanomaterial into a photovoltaic synergist coating and / or directly combining it with a photovoltaic substrate to increase the power generation efficiency of the photovoltaic panel, and the efficiency can reach 5%-15%.
[0044] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0045] Compared with the prior art, the present invention has the following beneficial effects:
[0046] (1) In the present invention, biochar is used as raw material. Different from the conventional hydrothermal synthesis method, the carbon nanomaterial is prepared by electrolysis, ultrasound and microwave circulation method. No subsequent chemical reagents are added, and the prepared carbon nanomaterial has good fluorescence properties. It can be combined with a photovoltaic substrate or directly used as a photovoltaic enhancer coating to improve the photothermal efficiency of photovoltaic panels. The phytoene carbon nanomaterials of apricot, rice straw and ganoderma lucidum prepared in the present invention can improve the photothermal efficiency by 9.2%, 8.1% and 13.8%, respectively.
[0047] (2) The technology for preparing carbon nanomaterials provided by the present invention is green and pollution-free, and has opened up a new path for the comprehensive utilization of biochar. In the preparation process, it will not generate huge energy consumption, nor will it make the preparation method too complicated and dangerous, and has high use value. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 This is a scanning electron microscope image (5 nm) of the carbon nanomaterial prepared in Example 1.
[0049] Figure 2 This is a scanning electron microscope image (5 nm) of the carbon nanomaterial prepared in Example 2.
[0050] Figure 3 This is a scanning electron microscope image (5 nm) of the carbon nanomaterial prepared in Example 3.
[0051] Figure 4 These are the 3D morphology detection result diagrams in the performance characterization section; Figure I is an AFM micrograph; Figure II is a stereogram; and Figure III is a histogram.
[0052] Figure 5 These are the EDS test result diagrams in the performance characterization section; Figure I is the sampling diagram; Figures II, III, and IV correspond to the carbon and oxygen content detection peak diagrams in the sampling range, respectively.
[0053] Figure 6 These are SEM images at different microscopic sizes in the performance characterization part; Figure I is 20μm; Figure II is 5μm; Figure III is 2μm; and Figure IV is 1μm. DETAILED DESCRIPTION
[0054] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and through specific implementation methods. However, the following examples are only simple examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.
[0055] In the following examples, unless otherwise specified, all reagents and consumables used were purchased from conventional reagent manufacturers in the field; unless otherwise specified, all experimental methods and technical means used were conventional methods and means in the field.
[0056] Example 1
[0057] This embodiment provides a method for preparing apricot phytoene carbon nanomaterial, which specifically comprises the following steps:
[0058] Step S1, putting the material powder after the effective components of apricot are extracted (i.e. apricot biomass) into water for ultrasonic cleaning, with a cleaning power of 600 W, a frequency of 25 kHz, and a time of 45 min, drying after removing impurities, and making a carbon plate through a carbon making process;
[0059] Step S2, directly subjecting the carbon plate obtained in S1 to electrolysis once, with a power of 300 W, a voltage of 40 V, a current of 20 A, and a duration of 5 days, to form a black suspension after stirring;
[0060] Step S3, subjecting the suspension to secondary electrolysis, ultrasound and microwave cycle treatment, and then centrifugally separating the suspension to remove non-fluorescent precipitates, thereby obtaining a carbon nanomaterial solution.
[0061] Among them, the electrolysis power is 300W, the voltage is 40V, the current is 20A, the ultrasonic stripping power is 800W, the frequency is 30kHz, and the microwave power is 300W; in this embodiment, ultrasonic stripping is performed after 12 hours of electrolysis, and then microwave treatment is performed for 12 hours after 12 hours. The three are repeated for a total time of 45 days.
[0062] The scanning electron microscope electron microscope of the carbon nanomaterial obtained by the above method is as follows Figure 1 As shown, the average particle size is 2.08±0.50nm.
[0063] Apricot's phytoene carbon nanomaterials are made into photovoltaic enhancer coatings and applied to silicon-based photovoltaic panels, which increases the photoelectric efficiency by 9.2%.
[0064] Example 2
[0065] A method for preparing rice straw phytoene carbon nanomaterials comprises the following steps:
[0066] Step S1, the powder obtained after the effective components of rice straw are extracted is put into water for ultrasonic treatment (power of 800 W, frequency of 20 kHz, time of 60 min), cleaned, dried after impurities are removed, and then made into carbon powder through a carbon making process.
[0067] Step S2, directly subjecting the carbon powder obtained in S1 to an electrochemical reaction (power 450 W, voltage 45 V, current 25 A, duration 7 days), and forming a black suspension after stirring.
[0068] Step S3, subjecting the suspension to electrolysis, ultrasound and microwave cycles, and then centrifugally separating the suspension to remove non-fluorescent precipitates, thereby obtaining a carbon nanomaterial solution.
[0069] The electrolysis power is 450W, the voltage is 45V, and the current is 25A; the power of the ultrasonic stripping is 800W, and the frequency is 20kHz; the microwave power is 400W. In this embodiment, ultrasonic stripping is performed after 24 hours of electrolysis, and then microwave treatment is performed for 24 hours after 24 hours. The three are repeated for 60 days.
[0070] The rice straw phytoene carbon nanomaterials are prepared by the above method. Figure 2 As shown, the average particle size is 3.05±0.30 nm.
[0071] The photovoltaic enhancer coating made of phytoene carbon nanomaterials from rice straw can be applied to silicon-based photovoltaic panels to increase the photoelectric efficiency by 8.1%.
[0072] Example 3
[0073] A method for preparing a phytoene carbon nanomaterial of Ganoderma lucidum comprises the following steps:
[0074] Step S1: The powder after the effective ingredients of Ganoderma lucidum are extracted is put into water and ultrasonicated (power is 750 W, frequency is 35 kHz, and time is 55 min) to clean it, remove impurities and then dry it, and then make it into carbon powder through carbon making process.
[0075] Step S2, directly subjecting the carbon powder obtained in S1 to an electrochemical reaction (power 900 W, voltage 48 V, current 30 A, duration 6 days), and forming a black suspension after stirring.
[0076] Step S3, subjecting the suspension to electrolysis, ultrasound and microwave cycle treatment, and then centrifugally separating the suspension to remove non-fluorescent precipitates, thereby obtaining a carbon nanomaterial solution.
[0077] The electrolysis power is 900W, the voltage is 48V, the current is 30A, the ultrasonic stripping power is 750W, the frequency is 35kHz, and the microwave power is 450W. In this embodiment, ultrasonic stripping is performed after 24 hours of electrolysis, and then microwave treatment is performed for 24 hours after 24 hours. The three are repeated for 55 days.
[0078] The phytoene carbon nanomaterial of Ganoderma lucidum is prepared by the method, and the average particle size is 1.5±0.20nm.
[0079] Ganoderma lucidum's phytoene carbon nanomaterials are built into the positive electrode surface of silicon-based photovoltaics, which can increase the photoelectric efficiency by 13.8%.
[0080] Comparative Example 1
[0081] The difference from Example 2 is that this comparative example refers to the method for preparing rice straw carbon quantum dots described in CN110157423A, and the specific steps are as follows:
[0082] (1) Wash the rice straw with deionized water, crush it with a grinder, wash it three times with anhydrous ethanol, and dry it;
[0083] (2) Take 1 g of the dried straw powder, place it in a crucible, put it in a muffle furnace, and calcine it at 400°C in air atmosphere for 60 min;
[0084] (3) The calcined sample was added with 30 mL of distilled water and ultrasonically vibrated for 30 min. The mixed solution after vibration was filtered with a 0.22 μm filter membrane to obtain an orange-yellow carbon quantum dot solution. After freeze-drying, a 10 mg / mL solution was prepared and stored at 4°C for use.
[0085] The average particle size of the carbon quantum dots prepared in this comparative example is about 2-5 nm.
[0086] Comparative Example 1 adopts a high-temperature calcination method. Compared with Example 2, it can be seen that no chemical reagents are added in the preparation method of the present invention, and no dangerous operating steps such as calcination are required. The average particle size of the obtained carbon quantum dots is more uniform than that of the comparative example, making its distribution on the photovoltaic panel or its combination with the substrate more uniform and stable, thereby improving the power generation efficiency.
[0087] Comparative Example 2
[0088] This comparative example refers to the preparation method of kudzu root carbon quantum dot material described in CN118792047A, in which the preparation method adopts a hydrothermal method.
[0089] (1) Collect a certain amount of kudzu root residue and dry it naturally in a ventilated place, and place it in a 60°C oven for 24 hours to completely remove moisture; fully grind the completely dried kudzu root residue, take 1 g of the powder obtained by grinding and disperse it in 10 mL of ultrapure water, and stir it magnetically at 1000 rpm for 20 hours to fully mix it, so as to obtain a pretreated biomass solution;
[0090] (2) Prepare 1 mol / L urea solution, take 10 mL and mix it with the pretreated biomass solution, place it in a sealed container and stir it magnetically at 1000 rpm for 15 min, immediately place it in a high-pressure reactor and send it into a 200°C oven to react for 6 h, cool to room temperature, centrifuge, take the supernatant and filter it through a 0.22 μm filter membrane to obtain Pueraria carbon quantum dots.
[0091] The particle size of the kudzu root carbon quantum dots obtained in this comparative example is 3-5 nm, of which 52.4% is distributed at 4 nm.
[0092] Therefore, comparative example 2 adopts the hydrothermal method. Compared with examples 1-3 of the present application, it can be seen that the preparation method of the present invention does not add any chemical reagents, does not require dangerous operating steps such as calcination, and the particle size is smaller than the particle size described in the comparative example.
[0093] Comparative Example 3
[0094] The difference from Example 1 is that the present comparative example does not carry out secondary electrolysis. The remaining steps are the same as those of Example 1.
[0095] That is, in the comparative example, the power of ultrasonic stripping is 800 W, the frequency is 30 kHz, and the microwave power is 300 W; after 12 hours of ultrasonic stripping, microwave treatment is performed for 12 hours, and the two are repeated for a total time of 45 days.
[0096] Comparative Example 4
[0097] The difference from Example 1 is that microwave is not used in this comparative example. The remaining steps are the same as those in Example 1.
[0098] The electrolysis power is 300W, the voltage is 40V, the current is 20A, the ultrasonic stripping power is 800W, and the frequency is 30kHz. In this embodiment, the ultrasonic stripping is performed for 12 hours after the electrolysis for 12 hours, and the two are repeated for a total of 45 days.
[0099] The carbon nanomaterials of apricot obtained in Comparative Examples 3 and 4 were tested to find that their particle sizes were larger than that of the carbon nanomaterial obtained in Example 1.
[0100] Therefore, the three treatment methods of electrolysis, ultrasound and microwave are cyclically carried out in the present invention, and none of them can be missing. Even if the treatment time is the same, the obtained product cannot reach the particle size obtained in the preparation method of the present invention. The reduction of particle size makes the obtained carbon nanomaterial have good fluorescence properties. Combining it with a photovoltaic substrate or directly using it as a photovoltaic synergist coating can significantly improve the photothermal efficiency of photovoltaic panels.
[0101] Performance Characterization
[0102] In the present invention, the apricot phytoene carbon nanomaterial prepared in Example 1 is taken as an example to characterize the performance of phytoene.
[0103] (1) 3D shape detection
[0104] AFM (Atomic Force Microscope) was used to detect the phytoene nanomaterials, and the results were as follows: Figure 4 As shown in FIG. 1, FIG. 2 and FIG. 3, it can be seen that the phytoene carbon nanomaterial prepared by the present invention has a curved surface structure.
[0105] (2) Carbon and oxygen content ratio
[0106] EDS test was used to detect the carbon and oxygen content ratio of phytoene nanomaterials. The results are as follows: Figure 5 As shown; Figure I in the figure shows the sampling range Spectrum 1, 2, 3; Figure II, Figure III and Figure IV correspond to the carbon and oxygen content detection peak diagrams of Spectrum 1, 2, 3 respectively. The specific results are shown in Table 1 below.
[0107] Table 1
[0108]
[0109]
[0110] (3) Microstructure and surface morphology
[0111] The present invention also uses SEM electron microscope measurement to conduct detailed observations on the microstructure of the phytoene nanomaterial at different microscopic sizes.
[0112] like Figure 6 As shown in the figure, Figure I is an electron microscope picture at 20μm, Figure II is 5μm, Figure III is 2μm, and Figure IV is 1μm; it can be seen from the figure that the microstructure of the phytoene nanomaterial is complex and the specific surface area is large.
[0113] In summary, the carbon nanomaterial preparation method provided by the present invention adopts electrolysis, ultrasound, and microwave cycle methods to prepare carbon nanomaterials without the subsequent addition of chemical reagents, and the prepared carbon nanomaterials have good fluorescence properties. Combining them with photovoltaic substrates or directly using them as photovoltaic enhancer coatings can improve the photothermal efficiency of photovoltaic panels.
[0114] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing biomass carbon nanomaterials, characterized in that: The preparation method uses biomass powder as raw material, obtains biochar suspension through carbonization and primary electrolysis, and then obtains the biomass carbon nanomaterial through secondary electrolysis, ultrasonic stripping and microwave circulation treatment.
2. The preparation method according to claim 1, characterized in that: The biomass powder is derived from any one or a combination of at least two of plant biomass, animal biomass, factory biomass or urban waste biomass; The biochar obtained after the biomass powder is processed into carbon is carbon powder, carbon rod or carbon plate.
3. The preparation method according to claim 2, characterized in that: The biomass powder is plant biomass, and the carbon nanomaterial prepared by taking the plant biomass as raw material is phytoene carbon nanomaterial.
4. The preparation method according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: Step S1, ultrasonically clean the biomass powder to remove impurities and then dry it to obtain biochar after charring; Step S2, electrolyzing the biochar obtained in step S1, and stirring to form a suspension; Step S3, subjecting the suspension obtained in step S1 to secondary electrolysis, ultrasonic stripping and microwave circulation treatment, and then to centrifugal separation to obtain a solution containing the biomass carbon nanomaterial.
5. The preparation method according to claim 4, characterized in that: The power of ultrasonic cleaning in step S1 is 500-1000W, the frequency is 20-40kHz, and the time is 30-60min; The method for making carbon in step S1 is as follows: under protective gas or vacuum conditions, the biomass powder is pressed into powder, rods or plates by a hydraulic press, and then carbonized and graphitized to complete the carbon making step.
6. The preparation method according to claim 4, characterized in that: In step S2, the power of one electrolysis is 100-1500W, the voltage is 0.01-48V, the current is 0.01-30A, and the duration is 2-7 days; In step S3, the secondary electrolysis power is 100-1500W, the voltage is 0.01-48V, and the current is 0.01-30A; The power of ultrasonic stripping in step S3 is 500-1000W and the frequency is 20-40kHz; The power of the microwave in step S3 is 300-1500W; In step S3, secondary electrolysis, ultrasonic stripping and microwave treatment are performed in a cycle for a total period of 24-60 days.
7. Biomass carbon nanomaterial prepared by the preparation method as described in any one of claims 1 to 6.
8. The biomass carbon nanomaterial according to claim 7, characterized in that: The average particle size of apricot phytoene carbon nanomaterials prepared from apricot biomass is 2.08±0.50nm; The rice phytoene carbon nanomaterials prepared from rice biomass have an average particle size of 3.05±0.30nm; The average particle size of the Ganoderma phytoene carbon nanomaterial prepared from Ganoderma biomass is 1.5±0.20nm.
9. Use of the biomass carbon nanomaterial according to claim 7 or 8 in the photovoltaic field.
10. The use according to claim 9, characterized in that: The applications include silicon-based photovoltaics, organic thin-film photovoltaics or perovskite photovoltaics.
Citation Information
Patent Citations
Method for producing carbon quantum dots on basis of straw and application
CN110157423A
Green preparation method of biomass carbon quantum dots capable of realizing rapid detection of hexavalent chromium ions in water
CN118792047A